ANALISIS PENGARUH INDEKS PERSEPSI KORUPSI DAN INDIKATOR MAKROEKONOMI TERHADAP INVESTASI ASING LANGSUNG DI NEGARA-NEGARA ASEAN TAHUN 2013-2022 - Ardina, Mayang; Astuti, Rini Dwi (FEB Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to analyze the effect of corruption perception index, market size, inflation, and trade openness on foreign direct investment in eight ASEAN countries in 2013-2022. The data used in this study are secondary data, namely data on foreign direct investment, corruption perception index, market size, inflation, and trade openness in eight ASEAN countries in 2013-2022. The analytical tool used in this research is panel data regression with Random Effect Model. The results of this study indicate that the corruption perception index variable has a negative and significant effect on foreign direct investment in eight ASEAN countries in 2013-2022, while the market size, inflation, and trade openness variables have a positive and significant effect on foreign direct investment in eight ASEAN countries in 2013-2022.